Lipid-Protein Interactions Methods and Protocols - Kleinschmidt, Jörg H.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Biological membranes are the essential structuring elements of all living cells. Many enzymatic reactions take place at the membrane-water interface. To gain detailed insight into membrane properties, it is therefore of great importance to understand the complex nature of the interactions of membrane proteins with lipids. Lipid-Protein Interactions: Methods and Protocols provides a selection of protocols to examine protein-lipid interactions, membrane and membrane protein structure, how membrane proteins affect lipids and how they are in turn affected by the lipid bilayer and lipid properties. The methods described here are all actively used, complementary, and necessary to obtain comprehensive information about membrane structure and function. They include label-free approaches, imaging techniques and spectroscopic methodologies. Written in the successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible protocols, and notes on troubleshooting and avoiding known pitfalls. Authoritative and easily accessible, Lipid-Protein Interactions: Methods and Protocols seeks to serve both professional and novices with its wide range of the methods frequently used in this area of research.
Quartz Crystal Microbalances as Tools for Probing Protein-Membrane Interactions -- Surface Plasmon Resonance for Measuring Interactions of Proteins with Lipid Membranes -- Probing the Thermodynamics of Protein-Lipid Interactions by Isothermal Titration Calorimetry -- Differential Scanning Calorimetry of Protein-Lipid Interactions -- Atomic Force Microscopy and Spectroscopy to Probe Single Membrane Proteins in Lipid Bilayers -- Optimized Negative-Staining Protocol for Lipid-Protein Interactions Investigated by Electron Microscopy -- Examining the Protein-Lipid Complexes using Neutron Scattering -- Circular-Dichroism and Synchrotron-Radiation Circular-Dichroism Spectroscopy as Tools to Monitor Protein Structure in a Lipid Environment -- Structural Characterization of Membrane Proteins and Peptides by FTIR and ATR-FTIR Spectroscopy -- Förster Resonance Energy Transfer as a Tool for Quantification of Protein-Lipid Selectivity -- A Guide to Tracking Single Transmembrane Proteins in Supported Lipid Bilayers -- Fluorescence Correlation Spectroscopy to Examine Protein Lipid Interactions in Membranes -- Analyzing Transmembrane Protein and Hydrophobic Helix Topography by Dual Fluorescence Quenching -- Studying Lipid-Protein Interactions with Electron Paramagnetic Resonance Spectroscopy of Spin-Labeled Lipids -- EPR Techniques to Probe Insertion and Conformation of Spin-Labeled Proteins in Lipid Bilayers -- Solid-State NMR Approaches to Study Protein Structure and Protein-Lipid Interactions -- Solution NMR Spectroscopy for the Determination of Structures of Membrane Proteins in a Lipid Environment -- Nanodiscs as a New Tool to Examine Lipid-Protein Interactions -- The Simulation Approach to Lipid-Protein Interactions.
Keywords: Proteins .; Lipids; Protein Science; Lipidology